PENGARUH PARTISIPASI ANGGOTA, KUALITAS PENGELOLA, KUALITAS PENGURUS, DAN PERANAN PEMERINTAH TERHADAP KEBERHASILAN USAHA KOPERASI. (KASUS KUD DI KABUPATEN BULELENG BALI) - RANTAU, KETUT (SOCA: Jurnal Sosial Ekonomi Pertanian; Vol. 2, No. 2 Juli 2002, 2012)
This research has been intended to find out the effects of member participation, management guilty, and Government Roles on Cooperatives performance, both the effect of the combination of those variables as well as the effect of individual variables are observed. Path analysis is used intensively in this study. This research was conducted in Buleleng regency, Cooperatives for samples taken were there those who have been concussed as KUD’S Mandiri. The members of KUD’s taken ware (n = 950) and the KUD’s management staff ware (n = 65) taken from the KUD’s for samples based on the term of the proportional allocation. Experiment using parth Analysis has show that, each of the variables (members Participation, the Management’s and of the Government’s roles) have positive effect and significant on the performance of the KUD’s.
Keywords: Cooperatives, Government Roles, Mamber Participation, Managament Guilty